Development and Implementation of a Novel Lifestyle Medicine Advanced Pharmacy Practice Experience Elective - Nicole D. Gillespie; Thomas L. Lenz (University of Minnesota Libraries Publishing, 2012)
Objective: To develop and implement an Advanced Pharmacy Practice Experience (APPE) to increase student's awareness and use of lifestyle modifications in chronic disease prevention and management. Design: A five-week APPE was developed that utilized a wide variety of activities, including direct patient care, patient education, case studies, journal clubs and reflective assessment and writing to explore various lifestyle modifications and their relation to chronic disease prevention and management. Conclusion: The novel lifestyle medicine APPE provides students a unique opportunity to advance their knowledge in therapeutic lifestyle changes and expand their understanding of the pharmacist's role in chronic disease prevention and management.   Type: Idea Paper